Cu-Ag alloy wire
By controlling the content and concentration difference of Ag in Cu-Ag alloy wires, and combining the tensile and heat treatment processes, the problem of insufficient embrittlement and bending fatigue resistance characteristics of alloy wires in heat treatment is solved, and the balance of high tensile strength, conductivity and bending fatigue resistance characteristics is achieved.
Patent Information
- Application Number
- CN202480003616.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-09
- Filing Date
- 2024-07-25
- Publication Date
- 2025-04-11
AI Technical Summary
The existing Cu-Ag alloy wire has aggravated embrittlement during heat treatment, making it difficult to achieve fine lineization, and the anti-flexural fatigue characteristics are insufficient during repeated bending use.
By controlling the content of Ag in the alloy composition to be 1.00 mass % or more and 6.00 mass % or less, and setting the surface annular region and a central region in the cross-section, the average concentration difference of Ag is controlled to be 1.00 mass % or more and 3.00 mass % or less, and combining with the tensile and heat treatment process, a Cu-Ag-based alloy wire with high tensile strength and high conductivity is formed.
The high tensile strength, high conductivity and excellent anti-bending fatigue characteristics of Cu-Ag alloy wire are realized, making it suitable for thinner wire applications and improving the cost competitiveness of the product.
Smart Images

Figure CN119816610A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Cu-Ag alloy wire. Background Art
[0002] Wires for electrical and electronic equipment are developing towards thinner single wire diameters, and copper alloy wires such as Cu-Sn, Cu-Cr, and Cu-Ag have begun to be used to replace pure copper wires with insufficient strength.
[0003] As electronic devices become more dense and smaller, the diameters of cables used to connect electrical and electronic devices and wires such as speaker coils are also becoming thinner. Among copper alloys, Cu-Ag alloys have excellent strength and electrical conductivity, and the balance between the two is also good.
[0004] For example, in the Cu-Ag alloy wire of Patent Document 1, the eutectic phase of Cu and Ag is stretched into a filament, thereby achieving high strength and high conductivity. In particular, Patent Document 1 shows a technology that develops a recrystallized aggregate structure through heat treatment during the process and achieves high strength through subsequent high processing. However, in Patent Document 1, since no appropriate wire drawing process is performed before the heat treatment, the embrittlement of the material during the heat treatment is aggravated, making it difficult to make thin wires, and due to poor production efficiency, it is difficult to become a cost-competitive product. In addition, no research has been conducted on the thinner Cu-Ag alloy wire to improve its properties that are not easily broken due to fatigue under repeated bending conditions (bending fatigue resistance).
[0005] Background Art Literature
[0006] Patent Literature
[0007] Patent Document 1: Patent No. 5051647 Summary of the invention
[0008] [Problems to be solved by the invention]
[0009] An object of the present invention is to provide a Cu-Ag alloy wire having high tensile strength and high electrical conductivity and excellent bending fatigue resistance.
[0010] [Technical means to solve the problem]
[0011] [1] A Cu-Ag alloy wire having an alloy composition containing 1.00 mass % to 6.00 mass % of Ag, with the remainder being Cu and inevitable impurities, having a metal structure including a Cu alloy phase as a parent phase and a second phase precipitate containing an Ag phase, wherein the tensile strength is 950 MPa or more when the Ag content is 1.00 mass % to less than 1.50 mass %, 1050 MPa or more when the Ag content is 1.50 mass % to less than 3.00 mass %, and 1060 MPa or more when the Ag content is 3.00 mass % to less than 5.00 mass %. In the case of containing 5.00 mass % to 6.00 mass % Ag, it is above 1200 MPa; in the case of containing 5.00 mass % to 6.00 mass % Ag, it is above 1450 MPa; in the cross section, when the straight-line distance from the surface to the center is set to L, the value (c1-c2) obtained by subtracting the average concentration c2 of Ag in the central area from the center to the surface to a length of 99L / 100 from the average concentration c1 of Ag in the surface annular area
[0012] [2] According to the Cu-Ag alloy wire described in [1], in a binary image obtained by graying the STEM dark field image of the cross section, binarizing the low brightness side to white, and binarizing the high brightness side to black, the average number density n1 (number / μm) of the black parts in the surface annular region is 2 ) relative to the average number density n2 (number / μm) of the black parts in the central area 2 ) ratio (n1 / n2) is greater than 2.0 and less than 6.0.
[0013] [3] The Cu—Ag alloy wire according to [1] or [2], wherein the alloy composition further contains a total of 0.05 mass % to 0.30 mass % of one or more elements selected from the group consisting of Sn, Mg, Zn, In, Ni, Co, Zr and Cr.
[0014] [4] The Cu—Ag alloy wire according to any one of [1] to [3], wherein the Cu—Ag alloy wire is a round wire having a diameter of 0.01 mm to 0.08 mm.
[0015] [5] The Cu—Ag alloy wire according to any one of [1] to [3], wherein the Cu—Ag alloy wire is a ribbon wire having a width of 0.020 mm to 0.320 mm and a thickness of 0.002 mm to 0.040 mm.
[0016] Effects of the Invention
[0017] According to the present invention, it is possible to provide a Cu-Ag alloy wire material having high tensile strength and high electrical conductivity and also excellent bending fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram for explaining the surface annular region and the central region in the cross section of the Cu-Ag alloy wire (round wire) according to the embodiment.
[0019] Figure 2 It is a schematic diagram for explaining a surface annular region and a central region in a cross section of a Cu-Ag alloy wire (ribbon wire) according to an embodiment.
[0020] Figure 3 This is a diagram for explaining counting the number of black portions in a binary image obtained from a STEM dark field image of the Cu—Ag alloy wire of Example 1. DETAILED DESCRIPTION
[0021] Hereinafter, the implementation manner will be described in detail.
[0022] The present inventors have repeatedly conducted active studies and have found that, by having a prescribed alloy composition, controlling the relationship between the average Ag concentration c1 in the surface annular region of the cross section and the average Ag concentration c2 in the central region, and controlling the tensile strength in the alloy composition within a prescribed range, the Cu-Ag alloy wire has high tensile strength and high electrical conductivity and is also excellent in bending fatigue resistance, and have completed the present invention based on this finding.
[0023] The Cu-Ag alloy wire of the embodiment has an alloy composition containing 1.00 mass% to 6.00 mass% of Ag, with the remainder being Cu and inevitable impurities, and has a metal structure including a Cu alloy phase as a parent phase and a second phase precipitate containing an Ag phase, and the tensile strength is 950 MPa or more when containing 1.00 mass% to less than 1.50 mass% of Ag, 1050 MPa or more when containing 1.50 mass% to less than 3.00 mass% of Ag, and 3000 MPa or more when containing 3.00 mass% to less than 1.50 mass% of Ag. In the case of 5.00 mass % Ag, it is not less than 1200 MPa, and in the case of containing 5.00 mass % to 6.00 mass % Ag, it is not less than 1450 MPa. In the cross section, when the straight-line distance from the surface to the center is set to L, the value (c1-c2) obtained by subtracting the average concentration c2 of Ag in the central area from the center toward the surface to a length of 99L / 100 from the average concentration c1 of Ag in the surface annular area. The value is not less than 1.00 mass % and not more than 3.00 mass %.
[0024] First, the alloy composition of the Cu-Ag alloy wire is described.
[0025] The Cu-Ag alloy wire of the described embodiment has an alloy composition containing 1.00 mass% or more and 6.00 mass% or less of Ag, with the balance being Cu and unavoidable impurities.
[0026] <Ag: 1.00 mass% or more and 6.00 mass% or less>
[0027] Ag (silver) is an element required to increase the tensile strength of the Cu-Ag alloy wire, and contains 1.00 mass% or more and 6.00 mass% or less of Ag. If the content of Ag is 1.00 mass% or more, the tensile strength of the Cu-Ag alloy wire can be increased due to the solid solution or precipitation of Ag. Moreover, if the content of Ag is 6.00 mass% or less, the decrease in the conductivity of the Cu-Ag alloy wire can be suppressed and the high conductivity of the Cu-Ag alloy wire can be maintained. Furthermore, if the content of Ag exceeds 6.00 mass%, it is difficult to add value to the customer's product because high strength cannot be achieved to match the cost increase of the material cost caused by the increase in the amount of Ag used. In order to achieve a balance between the increase in the tensile strength and the increase in the conductivity of the Cu-Ag alloy wire, the content of Ag is 1.00 mass% or more, preferably 1.50 mass% or more, and on the other hand, it is 6.00 mass% or less, preferably 4.00 mass% or less.
[0028] <Sub-components of the Cu-Ag alloy wire: 0.05 mass% or more and 0.30 mass% or less>
[0029] The alloy composition of the Cu-Ag alloy wire can also contain one or more elements selected from the group consisting of Sn, Mg, Zn, In, Ni, Co, Zr, and Cr in a total amount of 0.05% by mass or more and 0.30% by mass or less. That is, in addition to Ag which is an essential basic component, the Cu-Ag alloy wire can also contain one or more components selected from the group consisting of Sn, Mg, Zn, In, Ni, Co, Zr, and Cr in a total amount of 0.05% by mass or more and 0.30% by mass or less as optional component sub-constituents. If the content of the sub-constituent is 0.05% by mass or more, the tensile strength characteristics of the Cu-Ag alloy wire will be improved, and in some elements, it will bring the effect of alleviating the brittleness of the Cu-Ag alloy wire. Moreover, if the content of the sub-constituent is 0.30% by mass or less, the electrical conductivity of the Cu-Ag alloy wire will not be significantly impaired. Therefore, the content of the sub-constituent is preferably 0.05% by mass or more, more preferably 0.08% by mass or more, still more preferably 0.10% by mass or more. On the other hand, it is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, still more preferably 0.20% by mass or less.
[0030] <Sn: 0.05% by mass or more and 0.20% by mass or less>
[0031] If the content of Sn (tin) is 0.05% by mass or more, it helps to improve the tensile strength of the Cu-Ag alloy wire. If the content of Sn is 0.20% by mass or less, the electrical conductivity of the Cu-Ag alloy wire will not be significantly impaired. Therefore, the content of Sn is preferably 0.05% by mass or more, more preferably 0.07% by mass or more, still more preferably 0.08% by mass or more, particularly preferably 0.10% by mass or more. On the other hand, it is preferably 0.20% by mass or less, more preferably 0.18% by mass or less, still more preferably 0.15% by mass or less, particularly preferably 0.12% by mass or less.
[0032] <Mg: 0.05% by mass or more and 0.20% by mass or less>
[0033] If the content of Mg (magnesium) is 0.05 mass% or more, it has the effect of contributing to the improvement of the tensile strength of the Cu-Ag alloy wire and alleviating the brittleness of the Cu-Ag alloy wire. If the content of Mg is 0.20 mass% or less, it will not significantly damage the electrical conductivity of the Cu-Ag alloy wire or the manufacturability during casting. Therefore, the content of Mg is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.20 mass% or less, more preferably 0.18 mass% or less, further preferably 0.15 mass% or less, particularly preferably 0.12 mass% or less.
[0034] <Zn: 0.05 mass% or more and 0.30 mass% or less>
[0035] If the content of Zn (zinc) is 0.05 mass% or more, it has the effect of contributing to the improvement of the tensile strength of the Cu-Ag alloy wire and alleviating the brittleness of the Cu-Ag alloy wire. If the content of Zn is 0.30 mass% or less, it will not significantly damage the electrical conductivity of the Cu-Ag alloy wire. Therefore, the content of Zn is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.30 mass% or less, more preferably 0.25 mass% or less, further preferably 0.20 mass% or less, particularly preferably 0.15 mass% or less.
[0036] <In: 0.05 mass% or more and 0.20 mass% or less>
[0037] If the content of In (indium) is 0.05 mass% or more, it contributes to the improvement of the tensile strength of the Cu-Ag alloy wire. If the content of In is 0.20 mass% or less, it will not significantly damage the electrical conductivity of the Cu-Ag alloy wire. Therefore, the content of In is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.20 mass% or less, more preferably 0.18 mass% or less, further preferably 0.15 mass% or less, particularly preferably 0.12 mass% or less.
[0038] <Ni: 0.05 mass% or more and 0.30 mass% or less>
[0039] If the content of Ni (nickel) is 0.05 mass% or more, it has the effect of contributing to the improvement of the tensile strength of the Cu-Ag alloy wire. If the content of Ni is 0.30 mass% or less, the conductivity of the Cu-Ag alloy wire is not significantly impaired. Therefore, the content of Ni is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.30 mass% or less, more preferably 0.25 mass% or less, further preferably 0.20 mass% or less, particularly preferably 0.15 mass% or less.
[0040] <Co: 0.05 mass% or more and 0.20 mass% or less>
[0041] If the content of Co (cobalt) is 0.05 mass% or more, it contributes to the improvement of the tensile strength of the Cu-Ag alloy wire. If the content of Co is 0.20 mass% or less, the conductivity of the Cu-Ag alloy wire is not significantly impaired. Therefore, the content of Co is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.20 mass% or less, more preferably 0.18 mass% or less, further preferably 0.15 mass% or less, particularly preferably 0.12 mass% or less.
[0042] <Zr: 0.05 mass% or more and 0.20 mass% or less>
[0043] If the content of Zr (zirconium) is 0.05 mass% or more, it has the effect of contributing to the improvement of the tensile strength of the Cu-Ag alloy wire and alleviating the brittleness of the Cu-Ag alloy wire. If the content of Zr is 0.20 mass% or less, the conductivity of the Cu-Ag alloy wire or the manufacturability during casting is not significantly impaired. Therefore, the content of Zr is preferably 0.05 mass% or more, more preferably 0.07 mass% or more, further preferably 0.08 mass% or more, particularly preferably 0.10 mass% or more. On the other hand, it is preferably 0.20 mass% or less, more preferably 0.18 mass% or less, further preferably 0.15 mass% or less, particularly preferably 0.12 mass% or less.
[0044] <Cr: 0.05 mass% or more and 0.20 mass% or less>
[0045] If the content of Cr (chromium) is 0.05% by mass or more, it helps to improve the tensile strength of the Cu-Ag alloy wire, and if the content of Cr is 0.20% by mass or less, the conductivity of the Cu-Ag alloy wire is not significantly impaired. Therefore, the content of Cr is preferably 0.05% by mass or more, more preferably 0.07% by mass or more, further preferably 0.08% by mass or more, and particularly preferably 0.10% by mass or more, while on the other hand, it is preferably 0.20% by mass or less, more preferably 0.18% by mass or less, further preferably 0.15% by mass or less, and particularly preferably 0.12% by mass or less.
[0046] <Remainder: Cu and inevitable impurities>
[0047] The remainder other than the above components is Cu (copper) and inevitable impurities. Inevitable impurities are components that are inevitably mixed in the manufacturing process, and depending on the content, may become a factor that reduces any one or more of the tensile strength, electrical conductivity and bending fatigue resistance of the Cu-Ag alloy wire, and may have an impact on the environment or cause material embrittlement. Therefore, the less the content of inevitable impurities, the better. As inevitable impurities, for example, elements such as S, Pb, Sb, and Bi can be listed. The upper limit of the content of the inevitable impurities is preferably less than 0.0001% by mass for each of the elements, and the total of the elements is preferably less than 0.0005% by mass.
[0048] The Cu-Ag alloy wire is a copper alloy wire having a metal structure of a Cu alloy phase as a parent phase and a second phase precipitate containing an Ag phase. The second phase precipitate precipitates in the Cu alloy phase as a parent phase and is composed of an Ag phase (Ag single phase) and the like.
[0049] Figure 1 It is a schematic diagram for explaining the surface annular region and the central region in the cross section of the Cu-Ag alloy wire (round wire) according to the embodiment. Figure 2 1 is a schematic diagram illustrating a surface annular region and a central region in a cross section of a Cu-Ag alloy wire (ribbon wire) according to an embodiment of the present invention. Figures 1-2As shown, in the cross section of the Cu-Ag alloy wire 1 perpendicular to the longitudinal direction, i.e., the cross section of the Cu-Ag alloy wire 1, when the straight-line distance from the surface 1a of the Cu-Ag alloy wire 1 to the center 1b of the Cu-Ag alloy wire 1 is L, the region from the surface 1a toward the center 1b to the length L / 100 is the surface annular region R1, and the region from the center 1b toward the surface 1a to the length 99L / 100 is the center region R2. Furthermore, the value (c1-c2) obtained by subtracting the average concentration c2 of Ag in the center region R2 from the average concentration c1 of Ag in the surface annular region R1 is 1.00 mass % or more and 3.00 mass % or less.
[0050] When the cross section of the Cu-Ag alloy wire 1 is a perfect circle, the straight line distance L from the surface 1a to the center 1b is constant, the surface annular region R1 is annular, and the center region R2 is a perfect circle. When the cross section of the Cu-Ag alloy wire 1 is not a perfect circle, the straight line distance L from the surface 1a to the center 1b is not constant. For example, in the case of Figure 2 When the cross section of the Cu-Ag alloy wire 1 is rectangular, the straight-line distance L is not constant, the surface annular region R1 is a rectangular annular region, and the central region R2 is a rectangle.
[0051] If the value (c1-c2) is within the above range, the tensile strength and bending fatigue resistance of the Cu-Ag alloy wire can be improved. In particular, when the Cu-Ag alloy wire is bent, the stress applied to the surface of the Cu-Ag alloy wire is stronger than the stress applied to the center of the Cu-Ag alloy wire. If the value (c1-c2) is 1.00 mass % or more, the tensile strength of the Cu-Ag alloy wire can be improved due to the increase in the amount of Ag solid solution in the surface annular region R1, and the strength of the surface of the Cu-Ag alloy wire increases, thereby improving the bending fatigue resistance. Moreover, if the value (c1-c2) is 3.00 mass % or less, the decrease in the tensile strength of the Cu-Ag alloy wire caused by the insufficient amount of Ag solid solution in the center region R2 can be suppressed, and the wire breakage of the Cu-Ag alloy wire can be suppressed.
[0052] Moreover, when the alloy composition contains 1.00 mass % or more and less than 1.50 mass % of Ag, the tensile strength of the Cu-Ag alloy wire is 950 MPa or more, preferably 1050 MPa or more. When the alloy composition contains 1.50 mass % or more and less than 3.00 mass % of Ag, the tensile strength of the Cu-Ag alloy wire is 1050 MPa or more, preferably 1150 MPa or more. When the alloy composition contains 3.00 mass % or more and less than 5.00 mass % of Ag, the tensile strength of the Cu-Ag alloy wire is 1200 MPa or more, preferably 1300 MPa or more. When the alloy composition contains 5.00 mass % or more and less than 6.00 mass % of Ag, the tensile strength of the Cu-Ag alloy wire is 1450 MPa or more, preferably 1550 MPa or more.
[0053] If the tensile strength of the Cu-Ag alloy wire is within the above range, even if the Cu-Ag alloy wire is an ultrafine wire having a thinner wire diameter than conventional wires, it is possible to achieve high-level and well-balanced tensile strength, electrical conductivity, and bending fatigue resistance.
[0054] Moreover, in Figures 1-2 In the binarized image obtained by graying the STEM dark field image of the cross section of the Cu-Ag alloy wire 1 shown in FIG. 1 , the average number density n1 (number / μm) of the black portion in the surface annular region R1 is 1. 2 ) relative to the average number density n2 (number / μm) of the black portion in the central region R2 2 ) ratio (n1 / n2) is preferably 2.0 or more and 6.0 or less.
[0055] In the manufacturing method of the Cu-Ag alloy wire, the tensile strength can be further improved by forming a black portion (hereinafter, also referred to as a black portion) in a binary image as a high-density fibrous precipitate when drawing the wire. If the ratio (n1 / n2) is within the above range, the tensile strength and bending fatigue resistance of the Cu-Ag alloy wire can be further improved. In particular, when the Cu-Ag alloy wire is bent, the stress applied to the surface of the Cu-Ag alloy wire is stronger than the stress applied to the center of the Cu-Ag alloy wire. Therefore, if the ratio (n1 / n2) is 2.0 or more, the tensile strength of the Cu-Ag alloy wire can be further improved due to the increase of the black portion in the surface annular region R1, and the strength of the surface of the Cu-Ag alloy wire increases, thereby further improving the bending fatigue resistance. In addition, if the ratio (n1 / n2) is 6.0 or less, the decrease in the tensile strength of the Cu-Ag alloy wire caused by the lack of the black portion in the center region R2 can be suppressed.
[0056] Furthermore, the Cu-Ag alloy wire is preferably a round wire having a diameter of 0.01 mm or more and 0.08 mm or less. In this case, the cross section of the Cu-Ag alloy wire is a circular shape having a diameter of 0.01 mm or more and 0.08 mm or less. Even if the Cu-Ag alloy wire is a round wire having a wire diameter within the above range, that is, the Cu-Ag alloy wire is an extremely fine round wire, it has high tensile strength and high conductivity, and is also excellent in bending fatigue resistance.
[0057] Moreover, the Cu-Ag alloy wire may be a strip wire having a width of 0.020 mm to 0.320 mm and a thickness of 0.002 mm to 0.040 mm. In this case, the cross section of the Cu-Ag alloy wire is a strip (rectangular) having a long side of 0.020 mm to 0.320 mm and a short side of 0.002 mm to 0.040 mm. Even if the Cu-Ag alloy wire is a strip wire having a size within the above range, that is, the Cu-Ag alloy wire is an extremely fine strip wire, it has high tensile strength and high conductivity, and also has excellent bending fatigue resistance.
[0058] The tensile strength, electrical conductivity, and bending fatigue resistance of the Cu-Ag alloy wire material in the strip wire do not vary significantly from the tensile strength, electrical conductivity, and bending fatigue resistance of the round wire Cu-Ag alloy wire material before being formed into a strip. That is, if the tensile strength, electrical conductivity, and bending fatigue resistance of the Cu-Ag alloy wire material before being formed into a strip are above the prescribed values, the tensile strength, electrical conductivity, and bending fatigue resistance of the Cu-Ag alloy wire material in the strip wire are above the prescribed values.
[0059] Thus, Cu-Ag alloy wires have high tensile strength and high electrical conductivity, and are also excellent in bending fatigue resistance, so they are very suitable for use in connecting cables for electrical and electronic equipment. This makes it easier to miniaturize electrical and electronic equipment, save space in the wire installation area, and increase signal wiring, which was not easy to achieve in the past, and contributes to the miniaturization of electrical and electronic products and the high added value.
[0060] Next, a method for producing a Cu—Ag alloy wire will be described.
[0061] In the manufacturing method of the Cu-Ag alloy wire, first, a casting process is implemented to obtain a rough drawn wire by dissolving, casting, and rolling the raw material in a manner to obtain a predetermined alloy composition. The cooling rate during casting solidification in the casting process is 10°C / s or more and 100°C / s or less. If the cooling rate exceeds 100°C / s, the unsolidified molten metal cannot effectively flow into the gap in the surface layer that has solidified first, so the value (c1-c2) of the Cu-Ag alloy wire finally obtained is less than 1.00% by mass. In addition, even if the heat treatment process described later is performed, the ratio (n1 / n2) is less than 2.00% by mass. On the other hand, if the cooling rate is less than 10°C / s, the value (c1-c2) of the Cu-Ag alloy wire exceeds 3.00% by mass, which is not preferred from the perspective of productivity or quality maintenance.
[0062] After the casting process, the first wire drawing process of cold drawing the wire is implemented at a processing rate of 50% to 90%. If the processing rate is less than 50%, a sufficient amount of crystallization of the fine black portion will not be caused in the heat treatment process described later. Moreover, if the processing rate is less than 50%, there is also a problem of void defect growth. On the other hand, if the processing rate exceeds 90%, it is difficult to perform wire drawing at a high processing rate in the second wire drawing process described later. Therefore, from the viewpoint of promoting the crystallization of a sufficient amount of fine black portion, inhibiting void growth, and thus fully ensuring the wire drawing processing room in the second wire drawing process of the subsequent process, the first wire drawing process is implemented at a processing rate of 50% to 90%.
[0063] Here, the processing rate is a value obtained by subtracting the cross-sectional area of the sample after wire drawing from the cross-sectional area of the sample before wire drawing, dividing the value by the cross-sectional area of the sample before wire drawing, and multiplying the result by 100 to express the value in percentage, and is represented by the following formula.
[0064] [Processing rate] = {([Cross-sectional area of the sample before wire drawing] - [Cross-sectional area of the sample after wire drawing]) / [Cross-sectional area of the sample before wire drawing]} × 100 (%)
[0065] The first wire drawing step can be performed by a known method such as wire drawing using a die. The first wire drawing process can be performed in one pass or in multiple passes until the target wire diameter is obtained.
[0066] After the first wire drawing process, a heat treatment process generally referred to as aging heat treatment is implemented for the purpose of crystallization of the black part. The heat treatment process is carried out at a holding temperature of 300°C to 400°C, a holding time of 10 seconds to 30 minutes, preferably 5 minutes to 30 minutes. If the holding temperature is less than 300°C or the holding time is less than 10 seconds, the formation of the black part will not occur sufficiently. On the other hand, if the holding temperature exceeds 400°C, the diffusion is promoted, and the value (c1-c2) is less than 1.00% by mass. Moreover, even if the holding time of the heat treatment process is extended, the precipitation and diffusion of the solute also proceed. If the holding time is from 10 seconds to 5 minutes, the precipitation on the surface of the wire is significantly carried out, and the ratio (n1 / n2) is greater than 2.0. If the holding time is from 5 minutes to 30 minutes, the ratio (n1 / n2) is greater than 2.0, and the precipitation of the entire wire becomes active, resulting in an increase in tensile strength. If the holding time exceeds 30 minutes, the value (c1-c2) will be less than 1.00 mass % due to the progress of diffusion.
[0067] The heat treatment step can be performed using a known method such as batch heat treatment, high-frequency heating, electric heating, continuous heat treatment such as process heating, or the like.
[0068] In addition, when heat treatment or aging heat treatment at a temperature higher than the holding temperature is performed, the subsequent solution treatment (generally 700 to 900°C, 10 minutes to 5 hours) will not be able to obtain a metal structure that meets the requirements of the Cu-Ag alloy wire of the embodiment, so it is not preferred. Moreover, such treatment may promote the elimination of segregation and the growth of void defects, so it is also not preferred.
[0069] After the heat treatment process, the second wire drawing process of cold drawing is performed at a processing rate of 99.700% or more and 99.998% or less after cooling. If the processing rate is less than 99.700%, the tensile strength cannot be fully increased. On the other hand, it is difficult to process the processing technology when the processing rate exceeds 99.998%. Therefore, the second wire drawing process is performed at a processing rate of 99.700% or more and 99.998% or less.
[0070] The second wire drawing process can be performed by a known method such as a wire drawing process using a die. The second wire drawing process can be performed in one pass or multiple passes until the target wire diameter is obtained. In this way, a round Cu-Ag alloy wire can be manufactured.
[0071] Furthermore, the above-mentioned manufacturing method is mainly a method for manufacturing a round wire, but by rolling the round wire manufactured by the above-mentioned manufacturing method to a predetermined thickness, a Cu—Ag alloy wire material in the form of a strip wire can also be manufactured.
[0072] According to the embodiment described above, by having a predetermined alloy composition, controlling the relationship between the average concentration c1 of Ag in the surface annular region of the cross section and the average concentration c2 of Ag in the central region, and the tensile strength in the alloy composition within a predetermined range within a predetermined range, a Cu-Ag alloy wire having high tensile strength and high electrical conductivity and excellent bending fatigue resistance can be obtained.
[0073] Although the embodiments have been described above, the present invention is not limited to the embodiments, but includes all aspects included in the concept of the present invention and the claims, and various modifications can be made within the scope of the present invention.
[0074] Example
[0075] Next, examples and comparative examples will be described, but the present invention is not limited to these examples.
[0076] (Examples 1-1 to 1-11, 2-1 to 2-11, 3-1 to 3-11, 4-1 to 4-11, 5-1 to 5-8 and Comparative Examples 1-1 to 1-6, 2-1 to 2-6, 3-1 to 3-6, 4-1 to 4-6, 5-1)
[0077] In order to obtain the alloy composition shown in Tables 1 to 5, a casting process was performed in which the raw materials were dissolved, cast, and rolled in the atmosphere to obtain a rough drawn wire with a wire diameter of 6 to 39 mm. In the casting process, the cooling rate during casting solidification was controlled to the values shown in Tables 1 to 5. Next, the rough drawn wire was cold drawn at the processing rate shown in Tables 1 to 5 to form a wire diameter of 4 to 9 mm. Next, heat treatment was performed at the holding temperature and holding time shown in Tables 1 to 5. In addition, comparative examples 1-2, 2-2, 3-2, 4-2, and 5-1 were not heat treated. After cooling, cold drawing was performed at the processing rate shown in Tables 1 to 5 to obtain a round Cu-Ag alloy wire having a wire diameter shown in Tables 6 to 10.
[0078] (Examples 1-12, 2-12, 3-12, 4-12)
[0079] In order to obtain the alloy composition shown in Tables 1 to 4, a casting process was performed in which the raw materials were dissolved, cast, and rolled in the atmosphere to obtain a rough drawn wire with a wire diameter of 6 to 39 mm. In the casting process, the cooling rate during casting solidification was controlled to the values shown in Tables 1 to 4. Next, the rough drawn wire was cold drawn at the processing rate shown in Tables 1 to 4 to form a wire diameter of 4 to 9 mm. Next, heat treatment was performed at the holding temperature and holding time shown in Tables 1 to 4. After cooling, the wire was cold drawn at the processing rate shown in Tables 1 to 4 to obtain a round wire Cu-Ag alloy wire. Next, the round wire Cu-Ag alloy wire was rolled to obtain a strip wire Cu-Ag alloy wire having the thickness and width shown in Tables 6 to 9.
[0080] In the following tables, data used as the basis for comparative examples are indicated by underlining and italics.
[0081] [Table 1]
[0082]
[0083] [Table 2]
[0084]
[0085] [Table 3]
[0086]
[0087] [Table 4]
[0088]
[0089] [Table 5]
[0090]
[0091] [evaluate]
[0092] The following measurements and evaluations were performed on the Cu—Ag alloy wires obtained in the examples and comparative examples. The results are shown in Tables 6 to 10.
[0093] [1] Tensile strength
[0094] The Cu-Ag alloy wires obtained in the examples and comparative examples (two wires, n=2) were used to perform a tensile test in accordance with JISZ 2241:2011, and the tensile strength was calculated by averaging the two measured values.
[0095] [2] Bending fatigue resistance
[0096] Using the Cu-Ag alloy wires obtained in the examples and comparative examples, repeated bending tests were performed in accordance with JIS H 0500 No. 4100. Specifically, since fatigue properties have wire diameter dependence, for Cu-Ag alloy wires having a wire diameter of less than 0.03 mm, Cu-Ag alloy wires having a wire diameter of more than 0.03 mm, and Cu-Ag alloy wires in the form of ribbon wires, the wire diameters of the Cu-Ag alloy wires such as the wires in the process were made uniform to 0.03 mm, thereby making the wire diameters of the Cu-Ag alloy wires used in the repeated bending tests uniform to 0.03 mm.
[0097] A round Cu-Ag alloy wire with a wire diameter of 0.03 mm was used as the test object. The radius R of the fixture at the bending fulcrum when the Cu-Ag alloy wire was bent was set to 6 mm. One end of the Cu-Ag alloy wire was fixed to be grasped, and a weight of 30 g was hung so that the other end of the Cu-Ag alloy wire would not bend. The number of times the Cu-Ag alloy wire broke was measured, and its average value (average bending life, n = 5) was evaluated to see whether it satisfied the relationship of the following equations 1 to 3.
[0098] If the value of the average bending life satisfies the following formula 1, the bending fatigue resistance is considered to be very good and is marked as "excellent"; if it does not satisfy formula 1 but satisfies formula 2, the bending fatigue resistance is considered to be excellent and is marked as "excellent"; if it does not satisfy formulas 1 to 2 but satisfies formula 3, the bending fatigue resistance is considered to be good and is marked as "good"; if none of formulas 1 to 3 are satisfied, the bending fatigue resistance is considered to be poor and is marked as "unqualified".
[0099] Formula 1: Average bending life ≧ 5900 × (Ag concentration in alloy composition) + 40000
[0100] Formula 2: Average bending life ≧ 5900 × (Ag concentration in alloy composition) + 20000
[0101] Formula 3: Average bending life ≧ 5900 × (Ag concentration in alloy composition) + 5000
[0102] [3] Electrical conductivity
[0103] The electrical conductivity was calculated by using the Cu-Ag alloy wires (n=2) obtained in the examples and comparative examples and measuring them in accordance with JIS H0505:1975 and averaging the two measured values.
[0104] [4] Average Ag concentration
[0105] The cross section perpendicular to the length direction of the Cu-Ag alloy wire obtained in the embodiment and the comparative example was subjected to thinning processing of the sample using the converged ion beam method (FIB: Focused Ion Beam method). SIINT-3050TB (manufactured by SII Nanotechnologies) was used in the processing, and the acceleration voltage of the Ga ion beam was set to 30 kV. After processing, Ar ion milling of the sample surface was performed at an acceleration voltage of 2 kV for 5 minutes to remove damage to the sample. In this way, a sample for observation was obtained.
[0106] An atomic resolution analysis electron microscope with an aberration correction function (ARM manufactured by JEOL Ltd.: JEM-ARM200F) was used. The acceleration voltage of the electron beam was set to 200 kV, and the observation area was set to a square with a side length of 130 nm. The surface annular area and the central area on the surface of the observation sample were observed, and high-angle scattering dark field (HAADF-STEM: High-angle Annular Dark Field Scanning TEM) images (STEM dark field images) of the surface annular area and the central area were obtained. Three places were randomly selected on the surface of the observation sample as the surface annular area and the central area as the observation area. Then, energy dispersive X-ray spectroscopy (EDX: Energy Dispersive X-ray spectroscopy) attached to STEM was performed on each STEM dark field image to measure the concentration of Ag in the surface annular area and the concentration of Ag in the central area. The three measured values were averaged, thereby calculating the average concentration c1 of Ag in the surface annular area and the average concentration c2 of Ag in the central area.
[0107] [5] Average number density of black parts
[0108] Using the image processing software "Image J (version v1.53k)", each STEM dark field image obtained was processed as follows to calculate the average number density of the black part. First, a 400 nm region was cut out from each STEM dark field image. 2 ~800nm 2 The cropped image (cropped image) is grayscaled within an arbitrary range. Then, in the histogram of the brightness values of the grayscaled image, the upper 0.5 to 2.0% is used as the threshold, and the low brightness side is binarized to white and the high brightness side is binarized to black. Furthermore, the black parts with less than 1 pixel are removed as noise, and then the area with continuous contours in the remaining black parts is regarded as one black part, and the number of black parts is counted. The number density of black parts is calculated by dividing the counted number of black parts by the area of the cropped image. Then, by averaging the three measured values, the average number density n1 of black parts in the surface annular area and the average number density n2 of black parts in the central area are obtained respectively.
[0109] [Table 6]
[0110]
[0111] [Table 7]
[0112]
[0113] [Table 8]
[0114]
[0115] [Table 9]
[0116]
[0117] [Table 10]
[0118]
[0119] The STEM dark field image of the Cu-Ag alloy wire obtained in Example 1 is shown in Figure 3 As shown in Tables 1 to 10 and Figure 3 As shown, in the Cu-Ag alloy wire of the embodiment, the alloy composition is within the prescribed range, the relationship between the average Ag concentration c1 in the surface annular region and the average Ag concentration c2 in the central region is within the prescribed range, and the tensile strength in the alloy composition within the prescribed range is within the prescribed range, so both the tensile strength and the electrical conductivity are high, and the bending fatigue resistance is excellent. On the other hand, in the Cu-Ag alloy wire of the comparative example, at least one of the alloy composition, the relationship between the average Ag concentration c1 and the average Ag concentration c2, and the tensile strength in the alloy composition within the prescribed range is outside the prescribed range, so at least one of the tensile strength, the electrical conductivity, and the bending fatigue resistance is poor.
[0120] Reference numerals
[0121] 1:Cu-Ag alloy wire
[0122] 1a: Surface of Cu-Ag alloy wire
[0123] 1b: Center of Cu-Ag alloy wire
[0124] L: The distance from the surface of the Cu-Ag alloy wire to the center of the Cu-Ag alloy wire
[0125] R1: Surface ring area
[0126] R2: Central Area
Claims
1. A Cu-Ag alloy wire, characterized in that: An alloy composition containing 1.00 mass % or more and 6.00 mass % or less of Ag, with the remainder being Cu and inevitable impurities, having a metal structure including a Cu alloy phase as a parent phase and a second phase precipitate containing an Ag phase, Tensile Strength When Ag is contained in an amount of 1.00 mass % or more and less than 1.50 mass %, the pressure is 950 MPa or more, When Ag is contained in an amount of 1.50 mass % or more and less than 3.00 mass %, the pressure is 1050 MPa or more, When containing 3.00 mass % or more and less than 5.00 mass % of Ag, it is 1200 MPa or more, When Ag is contained in an amount of 5.00 mass % to 6.00 mass %, the pressure is 1450 MPa or more. In the cross section, when the straight-line distance from the surface to the center is set to L, the value (c1-c2) obtained by subtracting the average concentration c2 of Ag in the central area from the center toward the surface to a length of 99L / 100 from the average concentration c1 of Ag in the surface annular area to the length L / 100 from the average concentration c1 of Ag (c1-c2) is greater than 1.00 mass% and less than 3.00 mass%.
2. The Cu-Ag alloy wire according to claim 1, characterized in that: In the binarized image in which the STEM dark field image of the cross section is grayed, the low brightness side is binarized to white, and the high brightness side is binarized to black, The average number density n1 (number / μm) of black parts in the surface annular area 2 ) relative to the average number density n2 (number / μm) of the black parts in the central area 2 ) ratio (n1 / n2) is greater than 2.0 and less than 6.
0.
3. The Cu-Ag alloy wire according to claim 1, characterized in that: The alloy composition further contains 0.05 mass % to 0.30 mass % in total of one or more elements selected from the group consisting of Sn, Mg, Zn, In, Ni, Co, Zr, and Cr.
4. The Cu-Ag alloy wire according to any one of claims 1 to 3, characterized in that The Cu—Ag alloy wire is a round wire having a diameter of 0.01 mm to 0.08 mm.
5. The Cu-Ag alloy wire according to any one of claims 1 to 3, characterized in that The Cu—Ag alloy wire is a ribbon wire having a width of 0.020 mm to 0.320 mm and a thickness of 0.002 mm to 0.040 mm.